Gut Microbiota‐Dependent Trimethylamine N‐oxide and Cardiovascular Outcomes in Patients With Prior Myocardial Infarction: A Nested Case Control Study From the PEGASUS‐TIMI 54 Trial. Issue 10 (18th May 2020) - Gencer, Baris; Li, Xinmin S.; Gurmu, Yared; Bonaca, Marc P.; Morrow, David A.; Cohen, Marc; Bhatt, Deepak L.; Steg, P. Gabriel; Storey, Robert F.; Johanson, Per; Wang, Zeneng; Hazen, Stanley L.; et al.
Abstract : Background: Trimethylamine N‐oxide (TMAO) may have prothrombotic properties. We examined the association of TMAO quartiles with major adverse cardiovascular events (MACE) and the effect of TMAO on the efficacy of ticagrelor. Methods and Results: PEGASUS‐TIMI 54 (Prevention of Cardiovascular Events in Patients With Prior Heart Attack Using Ticagrelor Compared to Placebo on a Background of Aspirin ‐ Thrombolysis in Myocardial Infarction 54) randomized patients with prior myocardial infarction to ticagrelor or placebo (median follow‐up 33 months). Baseline plasma concentrations of TMAO were measured in a nested case‐control study of 597 cases with cardiovascular death, myocardial infarction, or stroke (MACE) and 1206 controls matched for age, sex, and estimated glomerular filtration rate [eGFR]. Odds ratios (OR) were used for the association between TMAO quartiles and MACE, adjusting for baseline clinical characteristics (age, sex, eGFR, region, body mass index, hypertension, hypercholesterolemia, diabetes mellitus, smoking, peripheral artery disease, index event, aspirin dosage and treatment arm), and cardiovascular biomarkers (hs‐TnT [high‐sensitivity troponin T], hs‐CRP [high‐sensitivity C‐reactive protein], NT‐proBNP [N‐terminal‐pro‐B‐type natriuretic peptide]). Higher TMAO quartiles were associated with risk of MACE (OR for quartile 4 versus quartile 1, 1.43, 95% CI, 1.06–1.93, P trend=0.015). The association was driven by cardiovascular death (OR 2.25, 95% CI, 1.28–3.96, P trend=0.003) and stroke (OR 2.68, 95% CI, 1.39–5.17, P trend<0.001). After adjustment for clinical factors, the association persisted for cardiovascular death (ORadj 1.89, 95% CI, 1.03–3.45, P trend=0.027) and stroke (ORadj 2.01, 95% CI, 1.01–4.01, P trend=0.022), but was slightly attenuated after adjustment for cardiovascular biomarkers (cardiovascular death: ORadj 1.74, 95% CI, 0.88–3.45, P trend=0.079; and stroke: ORadj 1.82, 95% CI, 0.88–3.78, P trend=0.056). The reduction in MACE with ticagrelor was consistent across TMAO quartiles ( P interaction=0.92). Conclusions: Among patients with prior myocardial infarction, higher TMAO levels were associated with cardiovascular death and stroke but not with recurrent myocardial infarction. The efficacy of ticagrelor was consistent regardless of TMAO levels. Registration: URL: https://www.clini​caltr​ials.gov ; Unique identifiers: PEGASUS‐TIMI 54, NCT01225562.